Proton-Coupled Organic Cation Antiporter-Mediated Uptake of Apomorphine Enantiomers in Human Brain Capillary Endothelial Cell Line hCMEC/D3 - Okura, Takashi; Higuchi, Kei; Kitamura, Atsushi; Deguchi, Yoshiharu (Biological & pharmaceutical bulletin, 2014)
R(−)-Apomorphine is a dopamine agonist used for rescue management of motor function impairment associated with levodopa therapy in Parkinson’s disease patients. The aim of this study was to examine the role of proton-coupled organic cation antiporter in uptake of R(−)-apomorphine and its S-enantiomer in human brain, using human endothelial cell line hCMEC/D3 as a model. Uptake of R(−)- or S(+)-apomorphine into hCMEC/D3 cells was measured under various conditions to evaluate its time-, concentration-, energy- and ion-dependency. Inhibition by selected organic cations was also examined. Uptakes of both R(−)- and S(+)-apomorphine increased with time. The initial uptake velocities of R(−)- and S(+)-apomorphine were concentration-dependent, with similar Km and Vmax values. The cell-to-medium (C/M) ratio of R(−)-apomorphine was significantly reduced by pretreatment with sodium azide, but was not affected by replacement of extracellular sodium ion with N-methylglucamine or potassium. Intracellular alkalization markedly reduced the uptake, while intracellular acidification increased it, suggesting that the uptake is driven by an oppositely directed proton gradient. The C/M ratio was significantly decreased by amantadine, verapamil, pyrilamine and diphenhydramine (substrates or inhibitors of proton-coupled organic cation antiporter), while tetraethylammonium (substrate of organic cation transporters (OCTs)) and carnitine (substrate of carnitine/organic cation transporter 2; (OCTN2)) had no effect. R(−)-Apomorphine uptake was competitively inhibited by diphenhydramine. Our results indicate that R(−)-apomorphine transport in human blood–brain barrier (BBB) model cells is similar to S(+)-apomorphine uptake. The transport was dependent on an oppositely directed proton gradient, but was sodium- or membrane potential-independent. The transport characteristics were consistent with involvement of the previously reported proton-coupled organic cation antiporter.